PENGGUNAAN OBAT GENERIK ANTI HIPERTENSI BERDASARKAN DATA PENJUALAN DI APOTEK K-24 BUARAN - Doni Iswandani; Rohima Robby; Ida Diana Sari; Ratna Amelia Ningsih (Jurnal Farmasi IKIFA, 2025)
The 2023 Indonesian Health Survey indicates that the prevalence of hypertension in individuals aged over 18 years, based on a doctor's diagnosis, is 13.22%, increasing to 55.23% in the 55-64 age group. Based on gender, the prevalence of hypertension is higher in women (36.85%) compared to men (31.34%), suggesting a greater risk for women. The purpose of this study was to determine the extent of antihypertensive drug use sold in pharmacies based on sales data. This study utilized a quantitative descriptive method to illustrate the use of generic antihypertensive drugs. The research was conducted at Apotek K-24 Buaran from May to June 2025. The population of this study was all sales data of generic antihypertensive drugs at Apotek K-24 Buaran during May – June 2025. The research sample was taken using the Total Sampling method, encompassing all sales data of generic antihypertensive drugs, both prescription and non-prescription, during that period. The results show that Amlodipine Besilate is the most frequently used antihypertensive drug in the pharmacy. The conclusion of this study is that in the prescription of generic antihypertensive drugs, the types of drugs found include Amlodipine, Candesartan, Nifedipine, Captopril, and Bisoprolol.